Surface Water Quality: A Case Study of Institut Teknologi Sepuluh Nopember Surabaya, Indonesia - Fadilla Azzahrani Puspa; Ira Shavina Inora Rahma (Tecno Scientifica Publishing, 2025)
This study evaluated the surface water quality at two lakes on the Sepuluh Nopember Institute of Technology (ITS) campus in Surabaya, Indonesia from October to December 2024. Water samples from ITS Lake Eight (SS1) and the ITS Student Dormitory Lake (SS2) were analyzed for eight parameters: Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), Dissolved Oxygen (DO), Total Dissolved Solids TDS, pH, temperature, Electrical Conductivity (EC), and turbidity. The results showed that COD, BOD, DO, and turbidity exceeded national quality standards at both locations, while TDS and pH remained within acceptable limits. SS2 exhibited poorer water quality than SS1 due to its proximity to dormitory drainage and domestic waste pollution. Seasonal variations significantly affected water quality, with BOD and COD increasing during the dry season and DO, TDS, and turbidity rising during the rainy season. The main pollution sources were organic matter decomposition and anthropogenic activities, leading to eutrophication and algal growth.